2023
DOI: 10.3389/fnut.2023.1291853
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a novel therapeutic strategy: the interplay between gut microbiota and high-fat diet in the pathogenesis of metabolic disorders

Xiaokang Jia,
Qiliang Chen,
Huiwen Wu
et al.

Abstract: In the past two decades, the rapid increase in the incidence of metabolic diseases, including obesity, diabetes, dyslipidemia, non-alcoholic fatty liver disease, hypertension, and hyperuricemia, has been attributed to high-fat diets (HFD) and decreased physical activity levels. Although the phenotypes and pathologies of these metabolic diseases vary, patients with these diseases exhibit disease-specific alterations in the composition and function of their gut microbiota. Studies in germ-free mice have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 248 publications
(287 reference statements)
0
2
0
Order By: Relevance
“…The balance between obligate and facultative anaerobes is essential for the integrity and function of the intestinal epithelial barrier; certain conditions, like antibiotic treatment or unhealthy lifestyles, may alter the gut microbiota composition, named dysbiosis, leading to the onset and development of different pathologies ( Naito, 2024 ). For example, the overgrowth of potentially harmful Proteobacteria , including Enterobacteriaceae , has been linked to the emergence of a pro-inflammatory microenvironment contributing to the pathogenesis of Inflammatory Bowel Diseases, as well as cancer and metabolic disorders like obesity, dyslipidaemia, type-2 diabetes, and non-alcoholic fatty liver disease ( Jia et al., 2023 ; Li et al., 2023a ). Specifically, it has been suggested that the relationship between the two dominant phyla, expressed as Firmicutes/Bacteroidetes ratio, may be associate to the development of metabolic diseases induced by high-fat diet ( Jia et al., 2023 ); also, certain bacteria in the intestine, such as Escherichia coli , Campylobacter jejuni , Fusobacterium nucleatum , and Bacteroides fragilis , have been described to express toxin proteins causing intracellular reactive oxygen species accumulation and DNA damage, and contributing to colorectal carcinogenesis ( Li et al., 2023a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance between obligate and facultative anaerobes is essential for the integrity and function of the intestinal epithelial barrier; certain conditions, like antibiotic treatment or unhealthy lifestyles, may alter the gut microbiota composition, named dysbiosis, leading to the onset and development of different pathologies ( Naito, 2024 ). For example, the overgrowth of potentially harmful Proteobacteria , including Enterobacteriaceae , has been linked to the emergence of a pro-inflammatory microenvironment contributing to the pathogenesis of Inflammatory Bowel Diseases, as well as cancer and metabolic disorders like obesity, dyslipidaemia, type-2 diabetes, and non-alcoholic fatty liver disease ( Jia et al., 2023 ; Li et al., 2023a ). Specifically, it has been suggested that the relationship between the two dominant phyla, expressed as Firmicutes/Bacteroidetes ratio, may be associate to the development of metabolic diseases induced by high-fat diet ( Jia et al., 2023 ); also, certain bacteria in the intestine, such as Escherichia coli , Campylobacter jejuni , Fusobacterium nucleatum , and Bacteroides fragilis , have been described to express toxin proteins causing intracellular reactive oxygen species accumulation and DNA damage, and contributing to colorectal carcinogenesis ( Li et al., 2023a ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the overgrowth of potentially harmful Proteobacteria , including Enterobacteriaceae , has been linked to the emergence of a pro-inflammatory microenvironment contributing to the pathogenesis of Inflammatory Bowel Diseases, as well as cancer and metabolic disorders like obesity, dyslipidaemia, type-2 diabetes, and non-alcoholic fatty liver disease ( Jia et al., 2023 ; Li et al., 2023a ). Specifically, it has been suggested that the relationship between the two dominant phyla, expressed as Firmicutes/Bacteroidetes ratio, may be associate to the development of metabolic diseases induced by high-fat diet ( Jia et al., 2023 ); also, certain bacteria in the intestine, such as Escherichia coli , Campylobacter jejuni , Fusobacterium nucleatum , and Bacteroides fragilis , have been described to express toxin proteins causing intracellular reactive oxygen species accumulation and DNA damage, and contributing to colorectal carcinogenesis ( Li et al., 2023a ). Furthermore, changes in pH values as well as the presence of histologic alterations of the gastric mucosa, as in chronic atrophic gastritis, were also associated to increased gut dysbiosis characterized by the prevalence of oral bacteria, like Rothia mucilaginosa , Streptococcus salivarius and Granulicatella adiacens ( Filardo et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%